EVALUASI DAERAH IRIGASI BENGAWAN JERO KABUPATEN LAMONGAN - Aris Setiawan; Nur Azizah Affandy (Litbang Pemas - Universitas Islam Lamongan, 2017)
Bengawan Jero Irrigation Area is located in the District Administration of Work Areas Karangbinangun, Lamongan.Objective of the research that for determine the level of damage that occurred in Bengawan Jero Irrigation Area and determine the priority scale rehabilitation of irrigation area of Bengawan Jero damage. Based on the analysis and discussion, analysis of priority rehabilitation of irrigation area of Bengawan Jero using Analytical Hierarchy Process (AHP) give first priority to sub-system 05 = 0.68. The next priority is a sub-system 07 = 0.44, subsystem 01 = 0.23, sub-system 09 = 0.70, sub-system 03 = 0.25, sub-system 10 = 0.42, sub-system 11 = 0.65 , sub-system 06 = 0.52, sub-system 08 = 0.54, sub-system 04 = 0.50 and last priority is the sub system 02 = 0.23. Selection of rehabilitation alternatives tailored to the available funds. If the available funds are insufficient for the rehabilitation of irrigation area Bengawan overall Jerothen rehabilitation can put emphasis on the primary channel only